Bullying in the Arts : Vocation, Exploitation and Abuse of Power. - Quigg, Anne-Marie (Taylor & Francis, 2016)
Diva, Prima Donna, Maestro, Virtuoso: creative geniuses with the ability to deliver artistic excellence. However this perception can serve to tilt the balance of power in relationships and to substantiate the notion of artistic temperament; the Master is always right and the Diva must have her way. The artistic genius may be hell to work with but the end result (the art) is exceptional, so behaviour deemed unacceptable in normal circumstances must be tolerated. If the corporate culture in the arts is in thrall to the concept of the artistic genius, then across the various disciplines within t.